Collaboration between a Pt-dimer and neighboring Co–Pd atoms triggers efficient pathways for oxygen reduction reaction. Issue 3 (4th January 2021) - Li, Haolin; Dai, Sheng; Bhalothia, Dinesh; Chou, Jyh-Pin; Hu, Alice; Chen, Tsan-Yao
Abstract : Charge localization via compression strain and electronegativity difference extracts electrons from Pd and Co, thereby opening efficient oxygen reduction pathways around the Pt dimer. Abstract : The development of electrocatalysts with reconcilable balance between the cost and performance in oxygen reduction reaction (ORR) is an imperative task for the widespread adoption of fuel cell technology. In this study, we proposed a unique model of diatomic Pt-cluster (Pt-dimer) in the topmost layer of the Co/Pd bimetallic slab (Co@Pd–Pt2 ) for mimicking the Cocore @Pdshell nanocatalysts (NCs) surface and systematically investigating its local-regional collaboration pathways in ORR by density functional theory (DFT). The results demonstrate that the Pt-dimer produces local differentiation from both ligand and geometric effects on the Co@Pd surface, which forms adsorption energy ( E ads ) gradients for relocating the ORR-adsorbates. Our calculations for E ads -variations of ORR-species, reaction coordinates, and intraparticle charge injection propose and confirm a novel local synergetic collaboration around the Pt-dimer in the Co@Pd–Pt2 system with the best-performing ORR behavior compared with all reference models. With proper selection of the composition in intraparticle components, the proposed DFT assessments could be adopted for developing economical and high-performance catalysts in various heterogeneous reactions.